Estratigrafia do Batólito Florianópolis, Cinturão Dom Feliciano, na Região de Garopaba-Paulo Lopes, SC - BITENCOURT, MARIA DE FÁTIMA; BONGIOLO, EVERTON MARQUES; PHILIPP, RUY PAULO; MORALES, LUIZ FERNANDO GRAFULHA; RUBERT, ROGÉRIO ROQUE; MELO, CLARISSA LOVATTO; LUFT, JOÃO LUIZ (Pesquisas em Geociências, 2008)
In southern Brazil, the Florianopolis Batholith results from prolonged, mainly granitic magmatism, as part of the Neoproterozoic Dom Feliciano Belt. Plutonic associations in this belt are related to transpressive tectonism (650-580 Ma) in post-collisional setting, where the translithospheric discontinuities of the Southern Brazilian Shear Belt have triggered magmatism, acting as channels for melts originated in deep crustal or mantle sources. In the region of Garopaba-Paulo Lopes, a fraction of this magmatism was studied, resulting in a formal proposition for its stratigraphic organization in igneous suites. A small volume of gneissic host rocks is found as roof pendants. The Paulo Lopes Suite comprises the foliated Paulo Lopes Granite, Garopaba Granitoids and Silveira Gabbro. It is characterized as porphyritic granitoids of high-K tholeiitic affinity, coeval with mafic, tholeiitic magmatism. It is followed by metaluminous, alkaline series granitoids of the Pedras Grandes Suite, namely the Vila da Penha Granite, comprising heterogranular and porphyritic facies, and the Serra do Tabuleiro Granite, comprising heterogranular, equigranular and porphyritic facies. The Cambirela Suite, last magmatic episode in the study area, encompasses alkaline plutonic, volcanic and subvolcanic rock types, as the Ilha Granite, the Cambirela Rhyolite and the Itacorumbi Granite. Hypabissal rocks are also part of this suite, and result from recurrent acid and basic magma pulses emplaced either as idividual dykes or composite ones. The magmatic associations described in this region attest to magma emplacement under a moderate to low stress field, possibly extinguished by the time the Cambirela Suite crystallized. Their age values indicate that they are mostly contemporaneous to the post-collisional, syntectonic magmatism of the Southern Brazilian Shear Belt, and the preservation of magmatic structures such as modal layering, relatively uncomon in granitoids, may also be attributed to their emplacement far from the main deformation sites. Features indicative of coeval mafic and felsic magmas are described in all three magmatic associations, and are especially significant in the Paulo Lopes and Cambirela suites. They attest to continuous mantle participation in the batholith construction.